Persuasive Strategies in WHO's Dengue Awareness Posters: ELM-Based Content Design in Vietnam - Do Thi Ha , Phuong (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2025)
Public health communication is essential for raising awareness and influencing behavior. In Vietnam, dengue fever remains a major health concern, with WHO-designed posters promoting prevention and management. However, their persuasive effectiveness remains underexplored. This study applies the Elaboration Likelihood Model (ELM) to analyze these posters and propose improvements. A qualitative content analysis of eight WHO dengue prevention posters published on Facebook (September 2022–2023) examined central cues (message clarity, logical argumentation, action-oriented guidance) and peripheral cues (visual appeal, emotional engagement, source credibility). Findings show a strong reliance on central cues, while peripheral elements—such as striking visuals and digital engagement—are underutilized, limiting persuasive impact. To enhance effectiveness, the study recommends improving visual appeal, incorporating emotional triggers, and optimizing digital engagement. These insights contribute to applying ELM in health communication and improving public health messaging in Vietnam.